THE DEVELOPMENT OF LEARNING ACHIEVEMENT IN SCIENCE SUBJECT USING 4 MAT LEARNING MANAGEMENT FOR GRADE 8 STUDENTS - Jangarun , Naruekorn; Pianchana, Techameth (Journal of Educational Review Faculty of Education in MCU, 2022)
This research article has the objectives to compare learning achievement of the students before and after using 4 MAT learning management; and to study the satisfaction of the students taught by 4 MAT learning management. The sample selected was 40 grade eight students from a classroom, collected using Cluster Random Sampling. The research instruments used consisted of a lesson plan using 4 MAT; a learning achievement test; and a questionnaire on the student satisfaction towards the leaning management. The data were analyzed using data analysis for the purpose of the research. According to the first objective, t-test for dependent samples was used while mean and standard deviation were used for finding the results of the second objective. The results revealed that the learning achievement of the grade eight students after learning through 4 MAT learning management was higher than the learning achievement prior to learning through 4 MAT with statistical significance at the .05 level. Besides, the results showed that the grade eight students were satisfied with learning through 4 MAT learning management at the highest level with an average of 4.61 and standard deviation of 0.03.